2018
DOI: 10.18203/2394-6040.ijcmph20182148
|View full text |Cite
|
Sign up to set email alerts
|

Study of substance use in teenage students in Miraj Town: a cross sectional descriptive study

Abstract: Background: Adolescence is recognized as the period for onset of behaviors and conditions that not only affect health limited to that time but also lead to adulthood disorders. Unhealthy behaviors such as smoking, drinking, and illicit drug use often begin during adolescence. Behavior patterns that influence health in adulthood have their origin in adolescence. The habit of substance use comes either from the peer groups or it may be generated within the family because the elders are resorting to one or the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…14 The habit of substance use comes either from the peer groups or it may be generated within the family because the elders are resorting to one or the other form of substance use. 15 In present study, it was revealed that most common factor determining substance use was addiction in family members (83.3%) followed by peer pressure (75%). A study done by Jasani et al described that most common reason for initiation of substance abuse was peer pressure, followed by pleasure, tension of study or grades.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…14 The habit of substance use comes either from the peer groups or it may be generated within the family because the elders are resorting to one or the other form of substance use. 15 In present study, it was revealed that most common factor determining substance use was addiction in family members (83.3%) followed by peer pressure (75%). A study done by Jasani et al described that most common reason for initiation of substance abuse was peer pressure, followed by pleasure, tension of study or grades.…”
Section: Discussionmentioning
confidence: 56%
“…A study done by Lokhande et al revealed that awareness regarding hazards of tobacco and alcohol use increased with advancing age and health education was one of the common measures suggested for controlling tobacco by study participants. 15 This study has a limitation that the findings cannot be generalized to the entire population, as it was specific to the male students enrolled for various courses of ITI. Prevalence of substance use in these students is a tip of iceberg; so future studies can be planned where actual situational analysis will be done at large scale to identify and address the factors affecting it.…”
Section: Discussionmentioning
confidence: 97%